A Survey on Smart Ambulance Traffic Control System -A Support for Implantable Medical Devices - Philip, Anu; Siml P, Thomas; Abraham, Neethan Elizabeth; Chandran, Reshma (International Journal of Computer Sciences and Engineering, 2025)
The growth of industrialization and urbanization has lead to an immense increase in the population invariably leading to rise in the number of vehicles on road. The resulting traffic congestion and traffic jams are the major hurdles for emergency vehicles such as ambulance carrying critical patients as these emergency vehicles are not able to reach their destination in time, resulting into a loss of human life. To solve this problem to some extent we have apparently come up with Intelligent Traffic Control System(TCS) for ambulance”. The proposed system clears the traffic congestion by turning all the red lights to green on the path of the ambulance, hence helping in clearing the traffic and providing way towards its destination. The system consists of an android application which registers the ambulance on its network. In case of emergency situation, if the ambulance halts on its way, the application sends an emergency command to the traffic signal server and also the direction where it wants to travel along with this the current position with the help of Global Positioning System (GPS). The nearest signal is identified based upon the current position of the ambulance. And that particular signal is made green till the ambulance passes by and later it regains its original flow of control. In this way it acts like a lifesaver project as it saves time during emergency by controlling the traffic lights.